2014
DOI: 10.1139/cjfr-2013-0375
|View full text |Cite
|
Sign up to set email alerts
|

Reversing legacy effects in the understory of an oak-dominated forest

Abstract: Current forests developed under conditions different from original forests, with higher deer densities, reduced fire frequency, denser canopies, and smaller canopy gaps. These alterations have led to understories dominated by species simultaneously browse tolerant, shade tolerant, and fire sensitive leading to difficulties in the regeneration of oak species (Quercus spp.) in some areas. We evaluated how three key processes -understory fire, canopy gaps, and browsing -influenced tree species in east central Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 61 publications
(82 reference statements)
3
20
0
Order By: Relevance
“…No tall oak saplings were recorded in controls. Our results are consistent with earlier studies of oak regeneration and effects of protection from browsing (Abrams, 2013;Bergquist et al, 2009;Jensen et al, 2012;Kelly, 2002;Pigott, 1983;Thomas-van Gundy et al, 2014). Exclosures were intentionally placed over relatively high density of oak seedlings and saplings; this was also true for controls, and the results of the BACI-test show that the density of oak seedlings and small oak saplings did not differ initially between controls and exclosures.…”
Section: Exclosures Favour Natural Oak Regeneration But Only Weaklysupporting
confidence: 91%
See 1 more Smart Citation
“…No tall oak saplings were recorded in controls. Our results are consistent with earlier studies of oak regeneration and effects of protection from browsing (Abrams, 2013;Bergquist et al, 2009;Jensen et al, 2012;Kelly, 2002;Pigott, 1983;Thomas-van Gundy et al, 2014). Exclosures were intentionally placed over relatively high density of oak seedlings and saplings; this was also true for controls, and the results of the BACI-test show that the density of oak seedlings and small oak saplings did not differ initially between controls and exclosures.…”
Section: Exclosures Favour Natural Oak Regeneration But Only Weaklysupporting
confidence: 91%
“…Mihók et al, 2009;Smit et al, 2012;Thomas-Van Gundy et al, 2014). Through their browsing preferences ungulates can reduce the abundance of some species, hence changing species composition of trees and other plants (Pellerin et al, 2010;Rooney and Waller, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…We evaluated deer browse rate as a function of management regime and fencing (open or caged) with Cox proportional hazard models implemented in the R statistical (R Core Team, 2016) package "coxme" (Therneau, 2015). We included initial oak height at planting and average vegetation height (for 2010 only) as covariates.…”
Section: Discussionmentioning
confidence: 99%
“…These regeneration failures, as in many other woody species, occur despite abundant mature oak trees that mast frequently followed by successful acorn germination. However, seedlings are unable to advance to the sapling stage, a pattern that can be reversed through fencing, suggesting that deer play an important role in preventing this transition (Abrams & Johnson, ; Leonardsson, Lof, & Gotmark, ; Long et al, ; Long, Pendergast, & Carson, ; Schwartz & Demchik, ; Thomas‐Van Gundy, Rentch, Adams, & Carson, ). These patterns suggested that selecting Q. rubra was an appropriate and sensitive indicator for assessing the outcome of our different deer management approaches.…”
Section: Methodsmentioning
confidence: 99%
“…Further, the case study stand contains a large number of generally non-merchantable trees (Ostrya virginiana) that may require removal to promote the regeneration of desirable tree species (e.g., oaks). Although one goal of management may be to promote higher quality deer habitat from the current mature forest, deer exclusion may also be necessary to control browsing on oak seedlings and saplings that are regenerating within canopy gaps [39]. Finally, small animal consumers of acorns produced by oak trees can complicate the desired goals associated with using silvicultural treatments that promote oak regeneration, particularly when the timing of harvest entries attempts to coincide with the periodicity of acorn production from mature trees [40].…”
Section: Discussionmentioning
confidence: 99%